2021
DOI: 10.1002/ajmg.a.62259
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac abnormalities in girls with Turner syndrome: ECG abnormalities, myocardial strain imaging, and karyotype–phenotype associations

Abstract: Turner syndrome (TS) is a chromosomal condition which is associated with an increased prevalence of cardiac morbidity and mortality. In this cross-sectional study, Minnesotabased electrocardiographic (ECG) abnormalities, aortic dimensions, routine-and myocardial strain echocardiographic parameters, and karyotype-cardiac phenotype associations were assessed in girls with TS. In total, 101 girls with TS (0-18 years) were included.The prevalence of major ECG abnormalities was 2% (T-wave abnormalities) and 39% had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In addition, the time of study conduction and the technological advances substantially influence the echocardiographic sensitivity of BAV in TS. Recent echocardiographic TS studies demonstrated a much higher BAV prevalence between 22% and 39% [43,44]. To overcome the limitation of suboptimal image quality, transesophageal echocardiography (TEE) might be applicable.…”
Section: Transthoracic and Transesophageal Echocardiographymentioning
confidence: 99%
“…In addition, the time of study conduction and the technological advances substantially influence the echocardiographic sensitivity of BAV in TS. Recent echocardiographic TS studies demonstrated a much higher BAV prevalence between 22% and 39% [43,44]. To overcome the limitation of suboptimal image quality, transesophageal echocardiography (TEE) might be applicable.…”
Section: Transthoracic and Transesophageal Echocardiographymentioning
confidence: 99%
“…The prevalence in our cohort study was within the limits reported by other authors (3.4-18.1%). 6,8,16,[23][24][25][26][27][28] In our group, in four of ten patients with coarctation of the aorta the diagnosis of TS was established late, after the age of 5 years, when the patients presented for endocrinological assessment for short stature. The mean age at diagnosis of TS in patients with coarctation of the aorta seemed to be lower compared to the patients with other various heart malformations (3.3 years vs. 6.3 years), although this association was not statistically signifi cant.…”
mentioning
confidence: 69%
“…The incidence of this malformation in TS varies between 6% and 41% in other studies. 6,8,16,[23][24][25][26][27][28] Increased prevalence of bicuspid aortic valve in individuals with monosomy X was demonstrated by other authors. 29,30 In TS the prevalence of bicuspid aortic valve is 30-50 higher than in general population and complete or partial loss of the second sex chromosome is the most likely predisposing factor.…”
mentioning
confidence: 75%
“…Due to the ongoing rapid growth and development of vascular morphology and body size in these patients, the evaluation of AD in children and adolescents needs to be adjusted based on BSA. This raises a pertinent question regarding the reference set: Previous studies have found that when healthy individuals are used as a reference, the incidence of AD by transthoracic echocardiography and magnetic resonance arteriography appears significantly higher than the theoretical value, reaching 30% and 16%, respectively [ 19 , 20 ]. Conversely, when using TS patients without cardiovascular lesions as a reference, the incidence of AD (TSZ-score ≥ 2) was notably much lower (2%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This raises a pertinent question regarding the reference set: Previous studies have found that when healthy individuals are used as a reference, the incidence of AD by transthoracic echocardiography and magnetic resonance arteriography appears significantly higher than the theoretical value, reaching 30% and 16%, respectively [ 19 , 20 ]. Conversely, when using TS patients without cardiovascular lesions as a reference, the incidence of AD (TSZ-score ≥ 2) was notably much lower (2%) [ 19 ]. In clinical practice, the evaluation of AD often demands the consideration of multiple parameters, such as ASI, A/D ratio, and TSZ-score.…”
Section: Discussionmentioning
confidence: 99%